A comparison of MyPKFiT and WAPPS‐Hemo as dosing tools for optimizing prophylaxis in patients with severe haemophilia A treated with Octocog alfa. Issue 3 (10th March 2021) - Arvanitakis, Alexandros; Berntorp, Erik; Astermark, Jan
Abstract: Introduction: MyPKFiT and the Web‐Accessible Population Pharmacokinetic service—Hemophilia (WAPPS‐Hemo) are web‐based population‐based applications developed for helping physicians individualize and optimize replacement therapy. Although MyPKFiT is intended for Octocog alfa and Rurioctocog alfa pegol use only, the WAPPS‐Hemo is applicable to all factor VIII concentrates. Aim: To compare MyPKFiT and WAPPS‐Hemo as dosing tools for optimizing treatment of patients with severe haemophilia A on regular prophylaxis with Octocog alfa in a real‐world setting. Methods: Fourteen patients with severe haemophilia A (median age 30.8 years; range 20–71) were enrolled. The FVIII activity was measured twice after a regular dose of Octocog alfa by the chromogenic and the one‐stage assays. PK analyses were performed using each tool and dosing estimations to reach trough levels of 1%, 3% or 5% after 48 h. Findings were calculated and compared. Results: The two PK algorithms yielded similar t ½ independent of the type of FVIII assay used. However, there were significant differences in the time to reach 1%, 3% and 5%. The WAPPS‐Hemo generated 10–12 h longer time to a trough of 1% and up to 4 h for the troughs of 3% and 5%. Accordingly, the doses estimated by WAPPS‐Hemo for a daily regimen were between 28% and 100% of those proposed by MyPKFiT. Conclusions: MyPKFiT and WAPPS‐Hemo provided similar half‐life estimations for Octocog alfa independent of the FVIII assay used. The doses suggested by WAPPS‐Hemo to reach specific troughs were overall lower, which may have implications for treatment optimization.